Nagaland's pig sub-sector: Current status, constraints and opportunities - Deka, Ram Pratim; Thorpe, W.R. (International Livestock Research Institute, 2008)
This report presents the results of a study which appraised the pig sub-sectors of three selected districts in Nagaland state, Northeast India. It synthesises the results from the three districts - Dimapur, Mon and Phek, and a market study in Kohima, draws conclusions and makes recommendations for research and development (R&D) interventions. To ensure consistency and comparable results, the same methodology was used in each of the district appraisals in Nagaland and in a similar study carried out in five districts of Assam and in Guwahati, Assam's capital. The report is divided into five main parts. Part one is introduction. Part two looks into Nagaland, livelihoods and the pig sub-sector. It discusses rural economy and the role of pigs. Part three discusses marketing of pigs and consumption of pork. Topics of discussion include prices of pork and factors affecting demand, price trends, level of consumption, future demand, current supply chain of pigs, and pork, output market, input market, projections of demand and supply of pork, food safety issues and main issues in consumption and marketing. Part four deals with pig production systems and discusses ethnic and socio-economic distribution, production systems and their classification, breeding and reproductive management, management of feeding, health management, and main issues in production systems. Part 5 summerises policy and institutional issues including regulatory environment, government and donor participation in the pig sub-sector, delivery of livestock services, and main policy and institutional issues.